Influence of Knowledge Management Process on Efficient and Effective Import Customs Clearance - มณีกูล, ฉัตรพล (Creative Business and Sustainability Journal, 2019)
This quantitative research aimed to study customs knowledge management processes i.e. customs knowledge acquisition, customs knowledge storage, customs knowledge distribution, and uses of customs knowledge that influenced on the efficient and effective import customs clearance. The researcher used constructed questionnaires to collect data from 316 samples who were the importers of automotive parts and accessories. The research findings show that the customs knowledge storage and uses of customs knowledge influenced positively on the efficient and effective import customs clearance, respectively. The importers should consider acquiring additional customs knowledge, applying customs knowledge to improve the import customs clearance processes, registering the past records of the customs clearance that were the organization’s specific learned lessons, and retaining customs specialists to enhance the efficient and effective import customs clearance.